2013
DOI: 10.7763/jocet.2013.v1.36
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulations of Nitric Oxide (NO) Formation in Methane, Methanol and Methyl Formate in different Flow Configurations

Abstract: This temperature favours prompt-NO formation, and therefore, a significant difference of the amount of NO (one order of magnitude higher) is observed in CH 4 as compared to oxygenated fuels due to low values of CH and N observed in these fuels (CH 3 OH and CH 3 OCHO). High flame temperatures (approximately 2900 K) due to high initial temperatures are observed in the homogeneous system. Therefore, in homogeneous system it was observed that the amount of NO produced by the three fuels is within the same order of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In Kioni et al [19], kinetic modeling study of NO formation in methyl formate flames in freely propagating flames, homogenous system and counter-flow diffusion flames at low pressures, 1 bar, and equivalence ratio of 1 showed low NO formation in this fuel when compared to the case of methane/air and methanol/air in all the three flow configurations. This is not in agreement with prior experimental investigations by Rao [20] and Gerhard et al [21] that have reported high NO formation in biodiesel.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In Kioni et al [19], kinetic modeling study of NO formation in methyl formate flames in freely propagating flames, homogenous system and counter-flow diffusion flames at low pressures, 1 bar, and equivalence ratio of 1 showed low NO formation in this fuel when compared to the case of methane/air and methanol/air in all the three flow configurations. This is not in agreement with prior experimental investigations by Rao [20] and Gerhard et al [21] that have reported high NO formation in biodiesel.…”
Section: Introductionmentioning
confidence: 87%
“…These variables are governed by mass conservation equation, momentum equations, species conservation equation, the energy equation and the equation of state. The full set of simplified governing equations and the assumptions resulting to their simplifications are available in Kioni et al[19].…”
mentioning
confidence: 99%